2020
DOI: 10.3389/fpsyt.2020.00542
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inpatient Psychotherapy for Patients With and Without Migratory Background: Do They Benefit Equally?

Abstract: Background: Research on the effectiveness of inpatient psychotherapy for migrant patients predominantly concludes that they have greater symptom severity at admission and benefit less from psychotherapy. This study aims to compare symptom severity and effects of psychotherapy regarding depression, somatoform disorders, anxiety disorders, and posttraumatic stress disorder (PTSD) in a sample of patients with and without migratory background (MB). Methods: Symptom severity of 263 patients (T0, pretreatment) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…This relation could be explained because parents' PTSD can impact the functioning of parenting (lower parenting satisfaction, less optimal parent-child relationships, and more frequent use of negative parenting practices, such as overt hostility and controlling behaviors [54]). In this context, it is necessary to develop interventions which help migrant women with PTSD, especially since some studies showed that patients with a migratory background did not benefit from psychotherapy as much as patients without a migratory background [55].…”
Section: Discussionmentioning
confidence: 99%
“…This relation could be explained because parents' PTSD can impact the functioning of parenting (lower parenting satisfaction, less optimal parent-child relationships, and more frequent use of negative parenting practices, such as overt hostility and controlling behaviors [54]). In this context, it is necessary to develop interventions which help migrant women with PTSD, especially since some studies showed that patients with a migratory background did not benefit from psychotherapy as much as patients without a migratory background [55].…”
Section: Discussionmentioning
confidence: 99%
“…At discharge 229 patients were counted as completers and therefore were included at remission analysis. For more information see: Kobel et al [ 60 ]. Among these we included 55 first- or second-generation immigrants at admission, and at discharge 48 were included in the analysis of PHQ-9 and 47 of PHQ-15.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent countries of origin were Poland (n = 10, 18.2%) and Turkey (n = 7, 12.7%). For more information see: Kobel et al [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations